EFFECT OF ASPECTS, ELEVATION, AND SLOPE GRADIENT ON ZAWITA FOREST UNDERSTORY VEGETATION COMPOSITION - Gailan Baper Ahmed; Ahmed Salih Khalaf; Saleem Ismael Shabaz (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
Vegetation diversity patterns are necessary to identify species of plants in the Zawita mountains area, Duhok Governorate, Iraq, to investigate the influence of topographical elements (aspects - north and south, elevations and slope gradients) on diagnosis, density, frequency, and species richness and diversity of species in the Zawita forest understory vegetation. Sampling vegetation was surveyed at (1 * 1 m-2), for 8 quadrats per each zigzag transect. The data were designed with a strip-strip block design, with four replicates for each transect. The results revealed significant differences in frequency, density, and Shannon index due to aspects, elevations, and slope gradient. While other measured traits, species richness, and Simpson index were not affected significantly. The highest density was recorded for the north-facing aspect at high altitude while the Shannon index diversity has existed in the south aspect at low elevation and low slope gradient.